(untitled) (Revista Internacional de Folkcomunicação, 2021)
This article is located in the field of folkcommunication, in a common point of literature, journalism and politics. It offers a thematic classification proposal for the cordel literature politic leaflet, based on the content analysis of poetic narratives of an informative-opinionated character elaborated on facts and themes of history and daily life, and called “de acontecidos” among other terms . Discusses data from a bibliographic review on the thematic diversity of cordel literature, with an emphasis on political leaflets, and questions quarrels that involve the methodological effectiveness of different classification models. Folkcommunication; Cordel literature; Journalism; Politics; Thematic classification.